Komparasi Algoritma C4.5 dan Naive Bayes Dalam Prediksi Penderita Penyakit Gagal Jantung - Robby Anggriawan; Handoyo Widi Nugroho (Jurnal SIMADA (Sistem Informasi dan Manajemen Basis Data), 2022)
Every year more than 36 million people die from Non-Communicable Diseases (PTM) (63% of all deaths). More than 9 million deaths from non-communicable diseases occur before the age of 60, and 90% of these “early” deaths occur in low- and middle-income countries. Globally PTM the number one cause of death each year is cardiovascular disease. Cardiovascular disease is a disease caused by impaired function of the heart and blood vessels, such as: coronary disease, heart failure or heart failure, hypertension and stroke. An estimated 17.3 million deaths are caused by cardiovascular disease.Keywords: C45 algorithm and naïve bayes algorithm; Rapid Miner;